(untitled) (Research, Society and Development, 2020)
The Psychiatric Reform brought a paradigm shift in psychosocial care in relation to the reorganization processes of the care model and daily practices in substitute services. Considering interdisciplinarity as an important strategy for the organization of work in Psychosocial Care Centers (CAPS), it becomes relevant to describe, contextualize and elucidate the perceptions of mental health professionals about deinstitutionalization and the experiences in the care of users served in this new model assistance. This is an exploratory-descriptive field research, with a phenomenological qualitative approach. The phenomenological interview was used for data collection. For data analysis, the Clark Moustakas method and interpretation in the Maurice Merleau-Ponty framework were used. The study was approved by the Research Ethics Committee of Universidade Federal Fluminense (UFF). The categories found were entitled: 1st) The meanings of deinstitutionalization for CAPS professionals, and 2nd) The deinstitutionalization of the patient’s human existence. In the research we describe the perceptions of the CAPS team, and the interdisciplinarity of professionals in the performance of this team in their daily lives, showing the importance of this exchange of knowledge, opinions and perceptions among professionals, in the form of more humanized care, realizing the uniqueness and the possibilities of users inserted in the new care model who need to reframe their existence and relearn how to live in society.